Flash-floods control - Silva, Emerson Luís Pawoski da; Silva, Maria Helena de Carvalho Rodrigues; Mendonça, Francisco de Assis (Electronic Journal "Fórum Ambiental da Alta Paulista", 2021)
Flash-Floods are among the hydrological disasters that most damage life and structures in Brazil. The frequency and impacts of flash-floods may become an increasing problem due to the future scenario of an increase in global temperature causing intense precipitation. Through the literature, the aim of this study was: clarify how flash-floods occur; present national policies and legal provisions related to disaster risk management and what actions are suggested for prevention and response. Flash-floods are intense water superficial movements that are not dependent on watercourses. They are depending of warm and humid climate, rugged terrain and waterproofing land cover. All over the planet, actions are proposed for these disasters. In Brazil, Civil Defense acts through monitoring, diagnosis, prognosis and structural actions, i.e., physical, and non-structural, or regulatory. The structural actions to flash-floods are focused on land cover and mainly vegetation, while non-structural actions focus on zoning risk areas and assisting of affected populations. These measurements can be improved with social data, as income, and meteorological data, as air mass movement, temperature, humidity and clouds. Information about flash-floods, responsible agencies and measures can be used to help manage the risk of these disasters.